Perbedaan Efektivitas Air Rebusan Jahe Dan Lemon Terhadap Frekuensi Mual Muntah Pada Ibu Hamil Trimester I Di Wiilayah Kerja Puskesmas Kelurahan Tembilahan Kota - Lastri, Lastri; Yuliani, Istri; Kasjono, Heru Subaris (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Background: Nausea vomiting is a physiological thing that often occurs in pregnant women in the first trimester. If left untreated it can cause excessive vomiting and nausea which can cause malnutrition, maternal weight loss, miscarriage, low birth weight, and premature birth. One way to deal with nausea and vomiting with non-pharmacology is ginger and lemon boiled water. Objective: To determine the difference in the effectiveness of ginger and lemon boiled water on the frequency of nausea and vomiting in first-trimester pregnant women. Method: This research design is quantitative with the quasi-experimental method, research design using two groups of pretest-posttest design. The sample number was 30 respondents with a purposive sampling technique. The instrument used an observation sheet measuring nausea vomiting (PUQE)-24.Statistical analysis using the Wilcoxon, Mann Whitney test. Results: Ginger boiled water is effective against the frequency of nausea and vomiting with a value of 0.000 (p<0.05), and lemon water with a value of 0.025 (p less than 0.05), and there is a difference in the effectiveness of ginger and lemon cooking water with a value of 0.048 (p less than 0.05). Conclusion: There are differences in the effectiveness of ginger and lemon cooking water. Ginger-boiled water is more effective against the frequency of nausea and vomiting in pregnant women in the first trimester than lemon water.